Clinico-haematological profile in COVID-19 patients: an observational study at tertiary care center (Journal of Pathology of Nepal, 2021)
Background: It is known as in other viral infections, severe acute respiratory syndrome coronavirus 2 infections, can be associated with haematological changes and often has the potential to optimize the monitoring of the infectious process and their severity. Hence, we took up this study to analyze clinico-haematological profiles in coronavirus disease-2019 patients and to compare haematological changes between mild, moderate, and severe cases.Materials and methods: The study included the patients who were tested positive for coronavirus disease-2019 infection and the patients were classified into mild, moderate and severe cases. The demographic data and the laboratory haematological parameters were collected and statistically analysed. The median values were compared between mild, moderate, and severe cases using non-parametric tests, Kruskal-Wallis test with posthoc Mann-Whitney, and the p-value was calculated using Chi-square test for statistical significance.Results:  Data was collected for 276 patients, of which 167 patients were mild cases, 50 were moderate and 59 were severe. The median was derived for all the haematological parameters in mild, moderate, and severe groups which showed an increasing trend in total leucocyte count, absolute neutrophil count, neutrophil to lymphocyte ratio, and a decreasing trend in absolute lymphocyte count and statistically significant with p-value